Penjadwalan Mata Pelajaran Menggunakan Metode Dynamic Programming (Studi Kasus SD Negeri 1 Babat Toman) - Riyanti, Rizki; Heriansyah, Rudi; Ramadhan, Mustafa (Jurnal Pengembangan Sistem Informasi dan Informatika, 2024)
Student subject scheduling is the process of selecting the optimal schedule for each student based on the availability of teacher Student subject scheduling is selecting the optimal schedule for each student based on the availability of teacher schedules, teacher teaching hours, and subjects adjusted to grade levels. Many methods, including the Dynamic Programming method, can be used to solve this problem. Dynamic Programming is an optimization method that solves problems into smaller sub-problems and saves sub-problem solutions to avoid resolving. In scheduling student subjects, this method can select the optimal schedule by solving problems into smaller subproblems. Using Dynamic Programming allows scheduling student subjects to be done more efficiently and quickly. Overall, using dynamic programming to schedule student subjects provides a better and more efficient solution than other methods. Therefore, this method benefits schools or educational institutions that want to create an optimal lesson schedule for their students.